2005
DOI: 10.1038/sj.onc.1208746
|View full text |Cite
|
Sign up to set email alerts
|

AID binds to transcription-induced structures in c-MYC that map to regions associated with translocation and hypermutation

Abstract: Translocation and aberrant hypermutation of c-MYC are common in B-cell lymphomas. Activation-induced Cytidine Deaminase (AID) initiates switch recombination and somatic hypermutation in B cells by targeted deamination of transcribed genes. We show that transcription of the immunoglobulin S regions and c-MYC results in formation of similar DNA structures, 'G-loops', which contain a cotranscriptional RNA: DNA hybrid on the C-rich strand and single-stranded regions and G4 DNA on the G-rich strand. AID binds speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
146
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 59 publications
(86 reference statements)
7
146
0
Order By: Relevance
“…Given that different nucleases, RAG or AID, are responsible for the various IGH cleavage sites, the fact that the JH breakpoints and switch m breakpoints did not differ with respect to their corresponding MYC breakpoint regions is unexpected and may suggest that a third mechanism is responsible for DNA cleavage in MYC; or that RAG and AID may cause cleavage in MYC breakpoint regions equivalently, possibly due to structural attributes of the MYC promoter region (see below). Duquette,19 recently demonstrated that AID targets to G-loops, co-transcriptional RNA: DNA hybrids on the C-rich strand and single-stranded regions and G4 DNA on the G-rich strand. 19 Similar distributions of RAG induced JH and AID induced switch m breakpoints does not necessarily argue against a prominent role of these G-loops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that different nucleases, RAG or AID, are responsible for the various IGH cleavage sites, the fact that the JH breakpoints and switch m breakpoints did not differ with respect to their corresponding MYC breakpoint regions is unexpected and may suggest that a third mechanism is responsible for DNA cleavage in MYC; or that RAG and AID may cause cleavage in MYC breakpoint regions equivalently, possibly due to structural attributes of the MYC promoter region (see below). Duquette,19 recently demonstrated that AID targets to G-loops, co-transcriptional RNA: DNA hybrids on the C-rich strand and single-stranded regions and G4 DNA on the G-rich strand. 19 Similar distributions of RAG induced JH and AID induced switch m breakpoints does not necessarily argue against a prominent role of these G-loops.…”
Section: Discussionmentioning
confidence: 99%
“…Duquette,19 recently demonstrated that AID targets to G-loops, co-transcriptional RNA: DNA hybrids on the C-rich strand and single-stranded regions and G4 DNA on the G-rich strand. 19 Similar distributions of RAG induced JH and AID induced switch m breakpoints does not necessarily argue against a prominent role of these G-loops. The clusters on MYC were quite wide and diffuse (560 and 779 bp in a 4555 bp region) compared to three sharply circumscribed peaks (10-15 bp in a region of 150 bp) described previously within Mbr of BCL-2 and attributed to RAG activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its high G content, the NT DNA strand at S regions could be stabilized by the formation of parallel four-stranded G quartets (17,18). Indeed, AID appears to bind specifically to G-loops within transcribed S regions (19) and can deaminate the displaced strand of a transcription-induced R-loop in vitro (20).…”
mentioning
confidence: 99%
“…[3][4][5], which have been implicated in several transcription-dependent phenomena (for example, see refs. [6][7][8][9].…”
mentioning
confidence: 99%